2020
DOI: 10.1186/s12915-020-00895-0
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 promotes Capicua degradation independently of ERK in the absence of ATXN1L

Abstract: Background Aberrations in Capicua (CIC) have recently been implicated as a negative prognostic factor in a multitude of cancer types through the derepression of targets downstream of the mitogen-activated protein kinase (MAPK) signaling cascade, such as oncogenic E26 transformation-specific (ETS) transcription factors. The Ataxin-family protein ATXN1L has previously been reported to interact with CIC in both developmental and disease contexts to facilitate the repression of CIC target genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Consistent with this observation, the inhibition of MAPK kinase (MEK), an upstream kinase of ERK, increases CIC levels in human cells treated with EGF ( Okimoto et al, 2017 ; Wang et al, 2017 ; Bunda et al, 2019 ). However, other studies have shown that EGF treatment does not induce CIC degradation in mammalian cells ( Ren et al, 2020 ; Wong et al, 2020 ), suggesting that the RTK activation-induced CIC degradation may depend on experimental conditions. Inactivation of MEK and p90RSK, a downstream kinase of ERK, suppresses the cytoplasmic translocation of CIC in HEK293T cells upon EGF or fibroblast growth factor treatment ( Ren et al, 2020 ).…”
Section: Introductionmentioning
confidence: 88%
“…Consistent with this observation, the inhibition of MAPK kinase (MEK), an upstream kinase of ERK, increases CIC levels in human cells treated with EGF ( Okimoto et al, 2017 ; Wang et al, 2017 ; Bunda et al, 2019 ). However, other studies have shown that EGF treatment does not induce CIC degradation in mammalian cells ( Ren et al, 2020 ; Wong et al, 2020 ), suggesting that the RTK activation-induced CIC degradation may depend on experimental conditions. Inactivation of MEK and p90RSK, a downstream kinase of ERK, suppresses the cytoplasmic translocation of CIC in HEK293T cells upon EGF or fibroblast growth factor treatment ( Ren et al, 2020 ).…”
Section: Introductionmentioning
confidence: 88%
“…It is of note that interaction of Efp and DDX5 requires SLC26A4-AS, suggesting the feature of Efp as an RNA-binding protein. In a study mainly using glioma cells, Efp was reported to be responsible for poly-ubiquitination and degradation of Capicua, a protein functioning as a transcriptional repressor of receptor tyrosine kinase signaling [ 42 ]. In this context, Efp has a tumor promotive effect.…”
Section: Roles Of Efp In Other Cancersmentioning
confidence: 99%
“…Previous studies have shown that the Capicua (CIC) protein has an important role as a prognostic factor in different types of cancer, and this role is related to changes in the expression of targets downstream of the MAPK signaling cascade[ 47 ]. However, a MAPK-independent mechanism has been proposed where the interaction of CIC with ATXN1L prevents CIC degradation by TRIM25[ 48 ]. Whereas TRIM25 repression increases CIC levels and its tumor suppressor function, TRIM25 induction decreases it, indicating that CIC degradation is mediated by TRIM25 via the UPS.…”
Section: Trim25 and Protein Ubiquitinationmentioning
confidence: 99%
“…Whereas TRIM25 repression increases CIC levels and its tumor suppressor function, TRIM25 induction decreases it, indicating that CIC degradation is mediated by TRIM25 via the UPS. TRIM25 is enriched in both ATXN1L knockout and knockdown cell systems[ 48 ]. Another CIC interacting protein is 14-3-3 sigma, which has been shown to act as a tumor suppressor by negatively regulating the cell cycle and causing G2/M arrest.…”
Section: Trim25 and Protein Ubiquitinationmentioning
confidence: 99%